Effect of Public Sector Financial Reforms on Budget Implementation in Nigeria - Daniel MARKUS (Journal of Accounting and Financial Management, 2026)
This study examines the effect of public sector accounting reforms on budget implementation in Nigeria, focusing on the adoption of International Public Sector Accounting Standards (IPSAS), Treasury Single Account (TSA), Government Integrated Financial Management Information System (GIFMIS), and Integrated Payroll and Personnel Information System (IPPIS). The study adopts descriptive and ex-post facto research design to investigate possible cause and effect relationship while inferential analysis was conducted using regression techniques with SPSS. The findings reveal that IPSAS adoption significantly improves budget execution and reporting accuracy by enhancing comparability, transparency, and fiscal credibility. TSA demonstrates a strong positive effect on budget implementation through consolidation of government revenues and minimization of leakages, thereby strengthening liquidity management. GIFMIS contributes positively by facilitating automated expenditure tracking and budgetary control, though with a relatively moderate effect compared to IPSAS and TSA. IPPIS also exerts a significant positive influence by eliminating ghost workers, ensuring payroll integrity, and generating fiscal savings, albeit with the smallest effect among the reforms. The study concludes that public sector accounting reforms collectively enhance transparency, accountability, and efficiency in Nigeria’s budget implementation process. It recommends strengthening IPSAS compliance, fully consolidating TSA operations, expanding the scope and infrastructure of GIFMIS, and updating IPPIS with robust biometric verification and continuous audits. These measures are essential for sustaining fiscal discipline, improving public financial management, and achieving credible budget outcomes.